Training Performed Above Lactate Threshold Decreases p53 and Shelterin Expression in Mice - de Carvalho Cunha, Verusca Najara; dos Santos Rosa, Thiago; Sales, Marcelo Magalhães; Sousa, Caio Victor; da Silva Aguiar, Samuel; Deus, Lysleine Alves; Simoes, Herbert Gustavo; de Andrade, Rosangela Vieira (International Journal of Sports Medicine, 2018)
Telomere shortening is associated to sarcopenia leading to functional impairment during aging. There are mechanisms associated with telomere attrition, as well to its protection and repair. Physical training is a factor that attenuates telomere shortening, but little is known about the effects of different exercise intensities on telomere biology. Thus, we evaluated the effects of exercise intensity (moderate vs. high-intensity domain) on gene expression of senescence markers Checkpoint kinase 2 and tumor suppressor (Chk2 and p53, respectively), shelterin telomere repeat binding 1 and 2 (Trf1/Trf2), DNA repair (Xrcc5), telomerase reverse transcriptase (mTERT) and telomere length in middle aged mice. Three groups were studied: a control group (CTL) and two groups submitted to swimming at intensities below the lactate threshold (LI group) and above the lactate threshold (HI group) for 40 and 20 min respectively, for 12 weeks. After training, the HI group showed reduction in p53 expression in the muscle, and decreased shelterin complex expression when compared to LI group. No differences were observed between groups for mTERT expression and telomere length. Thus, exercise training in high-intensity domain was more effective on reducing markers of senescence and apoptosis. The higher intensity exercise training also diminished shelterin expression, with no differences in telomere length and mTERT expression. Such results possibly indicate a more effective DNA protection for the higher-intensity exercise training.
Keywords: Telomere; aging; muscle mass; chronic exercise; apoptosis; swimming